Post-trial follow-up methodology in large randomized controlled trials: a systematic review protocol - Llewellyn-Bennett, Rebecca (Syst Rev, 2016)
BACKGROUND: Clinical trials typically have a relatively short follow-up period, and may both underestimate potential benefits of treatments investigated, and fail to detect hazards, which can take much longer to emerge. Prolonged follow-up of trial participants after the end of the scheduled trial period can provide important information on both efficacy and safety outcomes. This protocol describes a systematic review to qualitatively compare methods of post-trial follow-up used in large randomized controlled trials. METHODS/DESIGN: A systematic search of electronic databases and clinical trial registries will use a predefined search strategy. All large (more than 1000 adult participants) randomized controlled trials will be evaluated. Two reviewers will screen and extract data according to this protocol with the aim of 95% concordance of papers checked and discrepancies will be resolved by a third reviewer. Trial methods, participant retention rates and prevalence of missing data will be recorded and compared. The potential for bias will be evaluated using the Cochrane Risk of Bias tool (applied to the methods used during the in-trial period) with the aim of investigating whether the quality of the post-trial follow-up methodology might be predicted by the quality of the methods used for the original trial. DISCUSSION: Post-trial follow-up can provide valuable information about the long-term benefits and hazards of medical interventions. However, it can be logistically challenging and costly. The aim of this systematic review is to describe how trial participants have been followed-up post-trial in order to inform future post-trial follow-up designs. SYSTEMATIC REVIEW REGISTRATION: Not applicable for PROSPERO registration. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13643-016-0393-3) contains supplementary material, which is available to authorized users.